Attitudes and Knowledge of, and Preferences for Learning about Cultural Competence: A Study of Pharmacy Students from One Australian Pharmacy Program - Gloria Nkhoma; Chiao Xin Lim; Gerard A. Kennedy; Ieva Stupans (MDPI AG, 2022)
Culturally and linguistically diverse populations, particularly asylum seekers, face challenges in accessing healthcare services. Pharmacists need to be capable of identifying and responding appropriately to the needs of diverse population groups. The aims of this study were to clarify student pharmacists': knowledge of, and attitudes to, asylum seekers; their understanding of themselves with regard to cultural competence; their exposure to culturally and linguistically diverse clinical settings; their potential receptivity to learning opportunities directed towards cultural competence; and the extent to which they interpreted the current curriculum as improving their cultural competence. Pharmacy students' viewpoints and perspectives were essential as emerging pharmacy professionals. This study employed mixed methods and convenience sampling. There were no significant (p > 0.05) associations between demographics and any of the survey items. Five themes emerged from the interviews: namely, exposure, formal vs. informal, positive views, conflict, and sufficiency. Pharmacy curriculum should ideally provide sufficient knowledge to meet culturally diverse healthcare consumers' needs, especially asylum seekers. The most efficacious models for teaching cultural competence are as yet still undetermined. Interactive learning in cultural competence was recommended as essential.